Development of an IgY-Based Treatment to Control Bovine Coronavirus Diarrhea in Dairy Calves - Bok, Marina (2023)
Bovine Coronavirus (BCoV) is a major pathogen associated with neonatal calf diarrhea. Standard practice dictates that to prevent BCoV diarrhea, dams should be immunized in the last stage of pregnancy to increase BCoV-specific antibody (Ab) titers in serum and colostrum. For the prevention to be effective, calves need to suck maternal colostrum within the first six to twelve hours of life before gut closure to ensure a good level of passive immunity. The high rate of maternal Ab transfer failure resulting from this process posed the need to develop alternative local passive immunity strategies to strengthen the prevention and treatment of BCoV diarrhea. Immunoglobulin Y technology represents a promising tool to address this gap. In this study, 200 laying hens were immunized with BCoV to obtain spray-dried egg powder enriched in specific IgY Abs to BCoV on a large production scale. To ensure batch-to-batch product consistency, a potency assay was statistically validated. With a sample size of 241, the BCoV-specific IgY ELISA showed a sensitivity and specificity of 97.7% and 98.2%, respectively. ELISA IgY Abs to BCoV correlated with virus-neutralizing Ab titers (Pearson correlation, R2 = 0.92, p < 0.001). Most importantly, a pilot efficacy study in newborn calves showed a significant delay and shorter duration of BCoV-associated diarrhea and shedding in IgY-treated colostrum-deprived calves. Calves were treated with milk supplemented with egg powder (final IgY Ab titer to BCoV ELISA = 512; VN = 32) for 14 days as a passive treatment before a challenge with BCoV and were compared to calves fed milk with no supplementation. This is the first study with proof of efficacy of a product based on egg powder manufactured at a scale that successfully prevents BCoV-associated neonatal calf diarrhea.